Alendronate induces anti-migratory effects and inhibition of neutral phosphatases in UMR106 osteosarcoma cells - Molinuevo, María Silvina (2007)
Bisphosphonates are nonhydrolysable pyrophosphate analogues that prevent bone loss in several types of cancer. However, the mechanisms of anticancer action of bisphosphonates are not completely known. We have previously shown that nitrogen-containing bisphosphonates directly inhibit alkaline phosphatase of UMR106 rat osteosarcoma cells. In this study, we evaluated the effects of alendronate on the migration of UMR106 osteosarcoma using a model of multicellular cell spheroids, as well as the alendronate effect on neutral phosphatases. Alendronate significantly inhibited the migration of osteoblasts in a dose-dependent manner (10−6–10−4 M). This effect was also dependent on calcium availability. The spheroid morphology and distribution of actin fibers were also affected by alendronate treatment. Alendronate dose-dependently inhibited neutral phosphatase activity in cell-free osteoblastic extracts as well as in osteoblasts in culture. Our results show that alendronate inhibits cell migration through mechanisms dependent on calcium, and that seem to involve inhibition of phosphotyrosine-neutral-phosphatases and disassembly of actin stress fibers.